Aplikasi Pengenalan Wajah Menggunakan Hough Transform Based Feature Extraction - Septian Triadi; Leo Willyanto Santoso; Rudy Adipranata (Jurnal Infra, 2017)
The face recognition is one of the important areas in the field of research. Facial recognition can be used in commercial and legal fields. Thus the development of new techniques for characteristic extracting using hough transform is performed.Applications using pre-processing consist of histogran equalization, unsharp masking, and edge detection before processing using hough transform. Then use the block-wise hough transform to split the image into blocks of images.From the results of face recognition testing is influence by the variation of the pose. For lighting variations improvised using pre-processing so that different kinds of lighting can be recognized